Pengaruh Kepemimpinan Terhadap Kinerja Guru SDI Puspa Bangsa - Markhaban Markhaban; Haya Haya (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
This research was conducted due to the lack of teacher performance at SDI Puspa Bangsa, so researchers used the leadership pattern of school principals by conducting experimental type research at SDI with a sample of 25 people using pre-questionnaire and post-questionnaire methods. Before distributing the questionnaire, it was tested for validity, normality and homogeneity. Meanwhile, the instruments in the principal's leadership pattern consist of planning, implementation, monitoring and evaluation. As for the results of the effects of leadership patterns, there are results. The average score obtained on teacher performance when the principal's leadership pattern is applied is 85.98, categorized as very high, so the significance level is 39.508 Sig. < 0.050. This means that there is a significant difference in the performance of teachers who follow the principal's leadership pattern, which is higher than in the pre-questionnaire results.